Influence Of Strategic Orientation On The Growth Of Micro And Small Furniture Manufacturing Enterprises In Kenya - Okello, Grace Adhiambo; Ngugi, Patrick Karanja; Odhiambo, Romanus (International Academic Journal of Innovation, Leadership and Entrepreneurship (IAJILE), 2018)
MSEs are an important segment of our economy. They contribute about 70% to Kenya’s GDP and over 80% of employment. Promotion of MSEs in the informal sector is viewed as a viable approach to development. However, reports indicate that MSEs are ranked highest to risk exposure related to management. The higher exposure to risk for the MSEs leads to high collapse rate that leads to loss of job and hence low economic development. Lack of entrepreneurial management was ranked highest among the risks by businesses in Kenya. Entrepreneurial management has been fronted as a key determinant for a firm’s growth and profitability. Therefore, this study sought to establish the influence of strategic orientation on growth of MSE in furniture manufacturing industry in Kenya. To achieve the objectives of this study, the study was guided by Contingency Theory and Schumpeter’s Theory of Innovation. The research approach adopted in this study was the mixed method. The target population of study was the 10,345 owners/manager of furniture manufacturing MSEs in Nairobi. A sample of 393 owner/managers of furniture business in Nairobi was selected using stratified random sampling. The study used a questionnaire for data collection purposes. Respondents filled in the questionnaire as the researcher waited. A drop and pick later method was employed too. The researcher did pilot testing the of research instrument to ensure its reliability and validity. The study generated both qualitative and quantitative data. The study also used multiple linear regression model to study the relationship between dependent variable growth of MSEs and independent variable strategic orientation. The study found that strategic orientation influences growth of micro and furniture manufacturing enterprises in Kenya
Keywords: Strategic orientation; Growth; Micro and small furniture manufacturing enterprises